Hello my friend
This is correct!
No, Thus
So
Hence
Yours
Rapha
Hi guys,
Have answered this question, but when I checked the final answer it should be 7 not 11. Can you help me with where I went wrong. Cheers.
(a) Expand ( x + ⅟x )² = x² + 2x⅟x + ⅟x₂
= x² + 2 + ⅟x₂
(b) Suppose that x + ⅟x = 3. Use part (a) to evaluate x² + ⅟x² without attempting to find the value of x.
( x + ⅟x )² = x² + 2 + ⅟x₂
If x + ⅟x = 3, then = ( x + ⅟x )²
= ( 3 )²
= 9
Thus x² + 2 + ⅟x₂ = x² + ⅟x₂ + 2
= 9 + 2
So x² + ⅟x₂ = 11